REKONSTRUKSI PERLINDUNGAN HUKUM KONSUMEN ATAS DARK PATTERNS LAYANAN BERLANGGANAN DIGITAL DI INDONESIA - Monaliza Kalalembang; Yimmy Octavian Yapri; Riris Siregar; Hendrico Dolok; Paltiada Saragi (Fakultas Hukum Universitas Kristen Indonesia, 2026)
The digital economy has transformed consumer access to goods and services via electronic platforms. While enhancing convenience, digitalization introduces manipulative business practices like